2016
DOI: 10.1177/1557988316675091
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ramadan Fasting on the Spirometric Data of Healthy Adult Males

Abstract: The few studies carried out on the effects of Ramadan fasting (RF) on spirometric values present contradictory conclusions. This study aimed at assessing whether RF affects healthy adults’ spirometric values. Twenty-nine nonsmoking healthy males (M ± standard error of mean [SEM] of age: 27 ± 1 years) who fasted during Ramadan (June 29-July 28, 2014) volunteered to the study. Three periods (before-Ramadan [June 23-25], mid-Ramadan [July 14-16] and after-Ramadan [August 11-14]) were selected for spirometry measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 29 publications
(72 reference statements)
1
46
0
Order By: Relevance
“…It was much more efficient to apply for a sample random sampling study, as done by Sarraf-Zadegan et al (2000) ( Table 1S ). Second, the noninclusion of a control-group of nonfasting patients could be considered a limitation because the interior validity of the results from this study and the variations in the data assessed cannot be attributed exclusively to RF ( Latiri et al, 2017 ). In this regard, it has to be underlined that attaining nonfasting groups in Muslim countries is problematic, due to religious principles.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It was much more efficient to apply for a sample random sampling study, as done by Sarraf-Zadegan et al (2000) ( Table 1S ). Second, the noninclusion of a control-group of nonfasting patients could be considered a limitation because the interior validity of the results from this study and the variations in the data assessed cannot be attributed exclusively to RF ( Latiri et al, 2017 ). In this regard, it has to be underlined that attaining nonfasting groups in Muslim countries is problematic, due to religious principles.…”
Section: Discussionmentioning
confidence: 97%
“…This study results partly confirm these of Zouari et al (2018) who concluded that RF did not bring about any significant changes in the spirometric data of stable COPD male patients, including the MMEF. The above issue was discussed in two previous studies including healthy or COPD adults ( Latiri et al, 2017 ; Zouari et al., 2018 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A systematic review of 35 studies 48 reported that Ramadan fasting produced a fairly small but significant weight loss (−1.24 kg; 95% confidence interval:)-1.60, -0.88 kg() in both sexes, with most of the weight loss then restored within a few weeks after Ramadan. 49 However, others failed to observe significant changes in body weight during Ramadan, 49 while some even described weight gain during this period 49 (Table 5); these inconsistencies may be due to varied eating routines, socioeconomic status, differences in the number of fasting hours, ethnicity, gender, and the health status and the medical history of participants. 37,48,50…”
Section: Fasting Protocols and Body Compositionmentioning
confidence: 99%